Pendidikan Islam Progresif : Studi Komparasi Pemikiran Muhammad Abduh, Ahmad Dahlan dan Rahmah El Yunusiyah - Robbany, Tholib; Sidiq Rifai, Afga (IAIN Kendari, 2025)
Abstract This study aims to examine the educational thought of three prominent Islamic reformers—Muhammad Abduh, Ahmad Dahlan, and Rahmah el-Yunusiyah—in the context of progressive Islamic education. The focus of this research is on how each figure reconstructs the Islamic education system to remain relevant to contemporary challenges through a progressive-reconstructionist approach. Employing a qualitative method with a library research approach, the primary sources analyzed consist of the works and ideas of the three reformers. The findings reveal that these thinkers share a common vision of educational reform grounded in the integration of religious and secular knowledge, emphasizing intellectual liberation and moral development. Muhammad Abduh advocated for rationality and freedom of thought in education; Ahmad Dahlan implemented integrative education through the Muhammadiyah movement; while Rahmah el-Yunusiyah pioneered women’s education based on humanistic Islamic values. Collectively, their contributions helped shape an Islamic educational paradigm that is responsive to societal change, inclusive, future-oriented, and gender-equitable. These findings are supported by contemporary studies highlighting the importance of curriculum integration and the strengthening of spiritual and moral values in Islamic education in the digital and global era. Keywords: Progressive Islamic education, Muhammad Abduh, Ahmad Dahlan, Rahmah el-Yunusiyah, philosophy of education, tajdid, reconstructionism.